The Impact of Agricultural Mechanization Development Project on the Yield of Wheat Crop: A Case Study of Punjab, Pakistan - Nadeem Ashraf, Muhammad; Zubair Ahmad Khan, Talha (Journal of Applied Research and Multidisciplinary Studies, 2020)
A traditional method known as iron triangle (time, cost, quality) was used to evaluate the success of projects in the past. A project was assumed to be successful if it had been completed within time, did not overrun its allocated budget and its outcomes satisfied the predetermined criteria. However, to evaluate the impact of any project considering merely its success is not enough, the impact of its product should also be appraised. Therefore, this study was conducted to evaluate the effectiveness of the program “Agricultural Mechanization Development Project” recently implemented in Punjab, Pakistan. For this purpose, Punjab province was categorized into three zones on the basis of agro-climatic conditions. Two districts were randomly selected from each zone. Face to face structured interviews were conducted to collect primary data from beneficiary farmers (n=210). Regression analysis was applied to evaluate the significance of mechanization. The research findings revealed that improvement in technical efficiency through the use of agriculture mechanization program has a significant effect on the production of wheat crop. It is suggested here that ‘Agricultural Mechanization’ and other such programs ought to be considered efficient tools to fight poverty, bring mprovement in socioeconomic conditions and promote income generating activities among rural communities.